Inadequate regulation of the requirements for the admissibility. The evidence general organic code of procedures - Rodriguez Montenegro, José Antonio (2025)
The General Organic Code of Procedures (COGEP) establishes the hearing as a procedure for the administration of justice, which requires lawyers to adopt a new procedural approach in the presentation of evidence. This article analyzes one of the previously detailed aspects, the admissibility of evidence, with regard to the admissibility requirements (relevance, relevance, usefulness). While it is true that doctrine is a source of law, it must contain a number of criteria regarding the admissibility requirements of evidence. This qualitative study, a systematic bibliographic review using historical-logical, documentary review, hermeneutical, and analysis-synthesis methods, aims to develop some considerations regarding evidence in this new code. Among the main findings are: the existence of evidence demonstrating that evidence has been present in judicial proceedings since before our era; The purpose of this is to convince the judge of the facts and circumstances; the announcement in the complaint of all evidence and the inclusion of documentary evidence; for the evidence to be assessed by the judge, it must be requested, produced, and incorporated within the terms established in the COGEP (General Code of the State of the European Union). The parties have the right to promptly know the evidence to be produced, to object in a reasoned manner, and to contradict it; new evidence may be introduced up until before the convening of the trial hearing.